Using enantioselective dispersive liquid–liquid microextraction for the microseparation of trans-cyclohexane-1, 2-diamine enantiomers. Issue 3 (15th March 2017) - Hashemi, Majid; Hadjmohammadi, Mohammad Reza
Graphical abstract: Abstract: A new chiral separation system effective for the enantioselective extraction of racemic trans -cyclohexane-1, 2-diamine is presented. Enantioselective dispersive liquid–liquid microextraction has been used for the chiral microseparation of trans -cyclohexane-1, 2-diamine, with a chiral azophenolic crown ether being identified as a versatile chiral selector. The influence of various process conditions on the extraction performance was studied experimentally. It was found that the operational selectivity in one extraction step is mainly related to the type and volume of the solvents, chiral selector concentration, extraction time, temperature of sample solution, and pH. At optimum conditions (300 μL of diethyl ether as the extraction solvent 1 mL of methanol as the disperser solvent, with 5 mmol L −1 chiral selector concentration, pH of the sample equal to 4.5, 30 min extraction time and a temperature of 10 °C), the distribution ratio of ( R, R )- and ( S, S )- trans -cyclohexane-1, 2-diamine was 18.3 and 1.8, respectively, while the enantioselectivity value of 10.2 was found at the optimum condition.